Kebutuhan Persediaan Minumum Beras di Sulawesi Selatan pada Perum Bulog Divre Sulawesi Selatan - Asyriah Arifunddin Arifunddin; Abd. Rahman Kadir; Sumardi Sumardi (Hasanuddin Journal of Business Strategy, 2019)
One issue of the decline in the performance of the agricultural sector is claimed due to changing the authority of BULOG in managing strategic food through trade system instruments.This study aims to analyze the system of rice supply Perum BULOG South Sulawesi in terms of the number of economic orders, minimum inventory, maximum inventory, and determining the point of reorder. This research was conducted at the Office of Public Logistics Bureau at Jln. Andi Pangeran Pettarani, Makassar. In research using data collection techniques by means of observation, literature study, interviews and documentation. Analysis of the data that has been selected is the Economic Order Quantity (EOQ). The results showed that from the calculation results to determine the economical amount of inventory using EOQ calculations, it is known that the costs of South Sulawesi Bulog raw material inventory in 2017 amounted to 235.41 tons with a ordering frequency of 310 purchases in one year. Whereas from 2017 the realization of the absorption of Bulog rice procurement in South Sulawesi in 2017 amounted to 324,554 tons, with an ordering frequency of 305 times with an average of 1,064 tons per order. If the company can implement the EOQ method can provide savings on raw material inventory costs and the accuracy in managing the amount of inventory. Based on the calculation of the safety stock, it can be seen that in 2017 Bulog must have a safety stock of rice in the warehouse of 18,264 tons to avoid a stock out. Based on the reorder point calculation, Bulog must reorder when the stock is 18,383 tons. The maximum inventory of rice that can be stored in a warehouse is 18,499 tons.